Respuesta :
Simplifying
4(q + 2) + -6 = 0
Reorder the terms:
4(2 + q) + -6 = 0
(2 * 4 + q * 4) + -6 = 0
(8 + 4q) + -6 = 0
Reorder the terms:
8 + -6 + 4q = 0
Combine like terms: 8 + -6 = 2
2 + 4q = 0
Solving
2 + 4q = 0
Solving for variable 'q'.
Move all terms containing q to the left, all other terms to the right.
Add '-2' to each side of the equation.
2 + -2 + 4q = 0 + -2
Combine like terms: 2 + -2 = 0
0 + 4q = 0 + -2
4q = 0 + -2
Combine like terms: 0 + -2 = -2
4q = -2
Divide each side by '4'.
q = -0.5
Simplifying
q = -0.5
4(q + 2) + -6 = 0
Reorder the terms:
4(2 + q) + -6 = 0
(2 * 4 + q * 4) + -6 = 0
(8 + 4q) + -6 = 0
Reorder the terms:
8 + -6 + 4q = 0
Combine like terms: 8 + -6 = 2
2 + 4q = 0
Solving
2 + 4q = 0
Solving for variable 'q'.
Move all terms containing q to the left, all other terms to the right.
Add '-2' to each side of the equation.
2 + -2 + 4q = 0 + -2
Combine like terms: 2 + -2 = 0
0 + 4q = 0 + -2
4q = 0 + -2
Combine like terms: 0 + -2 = -2
4q = -2
Divide each side by '4'.
q = -0.5
Simplifying
q = -0.5
4(q + 2) - 6 = ?
Distribute the 4
4q + 8 - 6
Add like terms
4q + 2
4q + 2 is the answer.
Distribute the 4
4q + 8 - 6
Add like terms
4q + 2
4q + 2 is the answer.